Restricted Hartree-Fock Calculations in Light Nuclei - Manning, Martin (My University, 1967)
Restricted Hartree-Fock calculations for light even-even nuclei have been carried out using simple effective interactions. The primary emphasis is on the nature of the intrinsic states, and, in particular, on the deformation of these states. In order to find the equilibrium deformations a representation of deformed cylindrically symmetric states is used. A self-consistent technique for finding the equilibrium size and shape is proposed. There is a strong secondary emphasis on the role of the effective interaction, and four rather different interactions are used. Two of these incorporate a dependence on the density on the nuclear system, and this density dependence improves the systematic behaviour of the energies and sizes of light nuclei.
Hartree-Fock Calculations
This thesis is missing pages 152 and 194, neither of which are in the other copies of this thesis. -Digitization Centre
Keywords: hartree-fock calculations; light nuclei; restricted hartree-fock calculations